Microenvironment‐Induced In Situ Self‐Assembly of Polymer–Peptide Conjugates That Attack Solid Tumors Deeply. Issue 14 (27th February 2019) - Cong, Yong; Ji, Lei; Gao, Yu‐Juan; Liu, Fu‐Hua; Cheng, Dong‐Bing; Hu, Zhiyuan; Qiao, Zeng‐Ying; Wang, Hao
Abstract: In cancer treatment, the unsatisfactory solid‐tumor penetration of nanomaterials limits their therapeutic efficacy. We employed an in vivo self‐assembly strategy and designed polymer–peptide conjugates (PPCs) that underwent an acid‐induced hydrophobicity increase with a narrow pH‐response range (from 7.4 to 6.5). In situ self‐assembly in the tumor microenvironment at appropriate molecular concentrations (around the IC50 values of PPCs) enabled drug delivery deeper into the tumor. A cytotoxic peptide KLAK, decorated with the pH‐sensitive moiety cis ‐aconitic anhydride (CAA), and a cell‐penetrating peptide TAT were conjugated onto poly(β‐thioester) backbones to produce PT‐K‐CAA, which can penetrate deeply into solid tumors owing to its small size as a single chain. During penetration in vivo, CAA responds to the weak acid, leading to the self‐assembly of PPCs and the recovery of therapeutic activity. Therefore, a deep‐penetration ability for enhanced cancer therapy is provided by this in vivo assembly strategy. Abstract : Reaching new depths : Polymer–peptide conjugates (PPCs) designed to undergo an acid‐induced increase in hydrophobicity with a narrow pH‐response range (from pH 7.4 to 6.5) underwent in vivo self‐assembly in the tumor microenvironment (see picture). The PPCs in single‐chain form can penetrate deeply into the tumor and self‐assemble into nanoaggregates at molecular concentrations around the IC50 values of the PPCs for enhanced cancer therapy.